Coated steel sheet and method for manufacturing same

By forming a film of organic resin and wax on the surface of the steel plate and adjusting its proportion and distribution, the cracks and mold wear problems in complex shape press molding are solved, and the press moldability and coating performance are improved, which is suitable for molding of complex shapes.

CN119136977AActive Publication Date: 2024-12-13JFE STEEL CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202380036461.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-07
Filing Date
2023-05-15
Publication Date
2024-12-13
Estimated Expiration
2043-05-15

AI Technical Summary

Technical Problem

The existing coated steel plates are prone to cracks and mold wear during the pressing and forming process of complex shapes, resulting in a decrease in productivity. The prior art such as mold surface treatment and high viscosity lubricant oil methods have problems of high cost and poor degreasing.

Method used

A film containing organic resin and wax is used to adjust the proportion and distribution of organic resin and wax in the film, the friction coefficient between the steel plate and the mold is reduced, the slipperiness and adhesion uniformity of the film are improved, and the deviation of local adhesion amount is reduced.

Benefits of technology

The friction coefficient between the steel plate and the mold is significantly reduced, cracks and mold wear are avoided, press molding is improved, it is suitable for molding of complex shapes, and maintains good film removal and adhesiveness during the coating process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119136977A_ABST
    Figure CN119136977A_ABST
Patent Text Reader

Abstract

Provided is a coated steel sheet having excellent press moldability. The coated steel sheet is provided with a base steel sheet and a coating film that is provided on at least one surface of the base steel sheet and contains an organic resin and a wax, the organic resin being at least one type selected from the group consisting of an acrylic resin, an epoxy resin, a urethane resin, a phenolic resin, a vinyl acetate resin, and a polyester resin. The wax is a polyolefin wax having a melting point of 100-145 DEG C and an average particle diameter of 3.0 [mu] m or less, the proportion of the wax in the coating film is 5-70% by mass, the deviation [sigma] 'of the adhesion amount of the coating film is 0.300 or less, and the adhesion amount [mu] W of the coating film is 0.3 g / m2 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a coated steel sheet, and more particularly to a coated steel sheet having excellent press formability. In addition, the present invention relates to a method for producing the coated steel sheet. Background Art

[0002] Steel sheets such as cold-rolled steel sheets and hot-rolled steel sheets are widely used in various fields. For example, in applications such as automobile bodies, steel sheets are generally press-formed before use. Therefore, the steel sheets are required to have excellent press-formability.

[0003] In recent years, in order to improve the design of the product, there is a tendency to press-form into a more complicated shape. In addition, in order to simplify the manufacturing process, in promoting the integration of parts, in this sense, there is also a tendency to press-form into a more complicated shape.

[0004] However, when a steel sheet is press-formed into a complex shape, the steel sheet may be unable to withstand the forming and may break, or die wear (diegalling) may occur during continuous press forming. As a result, the productivity of products such as automobiles is seriously adversely affected. Therefore, it is required to further improve the press formability.

[0005] As a method for improving press formability, for example, a method of surface treating the mold used in press forming can be cited. Although this is a widely used method, there is a problem that once the surface treatment is performed, the mold cannot be adjusted afterwards. In addition, there is also a problem of high cost.

[0006] As a method for improving press-forming properties without performing surface treatment on the mold, there is a method of using high-viscosity lubricating oil. However, since the press-formed parts obtained by this method are in a state where the high-viscosity lubricating oil adheres, degreasing may be poor after press-forming. If degreasing is poor, the paintability is deteriorated.

[0007] Therefore, it is required to improve the press formability of the steel sheet itself instead of surface treatment of the mold and high-viscosity lubricating oil.

[0008] As a technique for improving the press formability of a steel sheet itself, it has been proposed to perform a surface treatment to form a lubricating film on the surface of the steel sheet.

[0009] For example, Patent Document 1 proposes a coated steel sheet in which an acrylic resin coating is formed on the surface of a galvanized steel sheet.

[0010] Patent Document 2 proposes that, in a coated metal sheet having a resin film formed on the surface of the metal sheet, a solid lubricant is made to protrude from the surface of the resin film by 0.01 to 1.5 μm.

[0011] Patent Document 3 proposes coating the surface of a metal product with a film having a thickness of 0.5 to 5 μm containing a lubricant in a polyurethane resin.

[0012] Patent Document 4 proposes a coated steel sheet having an alkali-soluble organic coating obtained by adding a lubricant to an epoxy resin.

[0013] Prior art literature

[0014] Patent Literature

[0015] Patent Document 1: Japanese Patent Application Laid-Open No. 09-170059

[0016] Patent Document 2: Japanese Patent Application Laid-Open No. 10-052881

[0017] Patent Document 3: Japanese Patent Application Publication No. 2000-309747

[0018] Patent Document 4: Japanese Patent Application Publication No. 2000-167981 Summary of the invention

[0019] However, in the techniques proposed in Patent Documents 1 to 4, although the lubricity is improved to a certain extent due to the effect of the lubricant contained in the film, the formability in complex press molding is not sufficient. Specifically, there are the following problems: cracks are generated in crack-prone areas during press molding, or mold wear is generated in areas where the surface pressure increases.

[0020] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a coated steel sheet having excellent press formability.

[0021] The present inventors paid attention to a coated steel sheet having a coating film composed of an organic resin and a wax and conducted intensive studies to solve the above-mentioned problems. As a result, they obtained the following findings.

[0022] (1) When a steel sheet formed with a film containing an organic resin and wax is press-formed, the film is scraped off by the mold when the film surface and the mold surface slide, and the lubricating film formed by the mixture of organic resin and wax in the film covers the mold surface and the sliding surface of the steel sheet. Therefore, in order to improve press-formability, it is necessary to improve the sliding property of the lubricating film covering the sliding surface of the mold surface and the steel sheet, that is, to reduce the friction coefficient.

[0023] (2) The friction coefficient can be significantly reduced by using specific organic resins and waxes and reducing local variations in the coating adhesion amount in the coating.

[0024] The present invention has been accomplished based on the above findings, and the gist of the present invention is as follows.

[0025] 1. A coated steel sheet comprising a base steel sheet and a coating film containing an organic resin and a wax provided on at least one surface of the base steel sheet, wherein:

[0026] The organic resin is at least one selected from acrylic resin, epoxy resin, polyurethane resin, phenolic resin, vinyl acetate resin and polyester resin.

[0027] The wax is a polyolefin wax having a melting point of 100°C to 145°C and an average particle size of 3.0 μm or less.

[0028] The ratio of the wax in the film is 5% to 70% by mass.

[0029] The deviation σ' of the coating adhesion amount defined by the following formula (1) is 0.300 or less.

[0030] The adhesion amount of the above film μ W 0.3g / m 2 above;

[0031]

[0032] Among them, W i : The amount of film deposited at the measuring point i (g / m 2 )

[0033] H i : The height of the base steel plate at the measuring point i,

[0034] μ W : The amount of film attached,

[0035] μ H : The average value of the height of the above-mentioned base steel plate,

[0036] a: the slope of the regression line in the scatter plot obtained by plotting the amount of the coating against the height of the base steel plate,

[0037] b: The intercept of the above regression line.

[0038] 2. The coated steel sheet according to item 1 above, wherein the ratio of the organic resin in the coating is 30% by mass to 95% by mass,

[0039] The ratio of the wax in the film is 5% by mass to 50% by mass.

[0040] 3. The coated steel sheet according to 1 or 2 above, wherein the arithmetic mean roughness Ra of the surface of the base steel sheet is 0.4 μm to 2.5 μm.

[0041] 4. The coated steel sheet according to any one of 1 to 3 above, wherein the coating has an adhesion amount of 2.5 g / m 2 the following.

[0042] 5. The coated steel sheet according to any one of 1 to 4 above, wherein the organic resin is an alkali-soluble resin.

[0043] 6. The coated steel sheet according to any one of 1 to 5 above, wherein the coating further contains a rust inhibitor.

[0044] 7. The coated steel sheet according to item 6 above, wherein the rust inhibitor is at least one selected from the group consisting of aluminum salts, zinc salts and zinc oxide of phosphoric acid.

[0045] 8. The coated steel sheet according to any one of 1 to 7 above, wherein the coating further contains a dispersant.

[0046] 9. The coated steel sheet according to 8 above, wherein the dispersant is at least one selected from the group consisting of sodium polycarboxylate, sodium polyacrylate, carboxylic acid copolymer and sulfonic acid copolymer.

[0047] 10. The coated steel sheet according to any one of 1 to 9 above, wherein the coating further contains silicon dioxide.

[0048] 11. A method for producing a coated steel sheet, which is the method for producing a coated steel sheet according to any one of 1 to 10 above, comprising applying a coating material comprising an organic resin and a wax to at least one surface of a base steel sheet and drying the coating material,

[0049] The organic resin is at least one selected from acrylic resin, epoxy resin, polyurethane resin, phenolic resin, vinyl acetate resin and polyester resin.

[0050] The wax is a polyolefin wax having a melting point of 100° C. to 145° C. and an average particle size of 3.0 μm or less.

[0051] 12. The method for producing a coated steel sheet according to 11 above, wherein the maximum reaching temperature of the base steel sheet during the drying is 60° C. to the melting point of the wax.

[0052] 13. The method for producing a coated steel sheet according to 11 or 12 above, wherein the ratio of the total solid content in the coating material is 1% by mass to 30% by mass.

[0053] According to the present invention, the friction coefficient between the steel plate and the die can be significantly reduced. As a result, according to the present invention, even for a portion that is prone to cracking during press forming, it is possible to form without cracking. In addition, according to the present invention, it is possible to suppress die wear at a portion with high surface pressure. Therefore, the coated steel plate of the present invention has extremely good press formability and can be well suited for forming into complex shapes. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 This is an example of a scatter plot of the coating adhesion amount with respect to the steel plate height for calculating σ'.

[0055] Figure 2 This is a schematic front view showing a friction coefficient measuring device.

[0056] Figure 3 Yes means Figure 2 A simplified three-dimensional diagram of the flange shape and size. DETAILED DESCRIPTION

[0057] Hereinafter, examples of embodiments of the present invention will be described. In the following description, unless otherwise specified, the unit "%" of content means "mass %".

[0058] (1) Coated steel plate

[0059] A coated steel sheet according to one embodiment of the present invention includes a base steel sheet and a coating provided on at least one surface of the base steel sheet.

[0060] [Membrane]

[0061] The film contains an organic resin and wax. Each component is described below.

[0062] (Organic resin)

[0063] In the present invention, the organic resin acts as a binder to hold the wax on the steel plate surface. Since the inorganic binder has a low affinity with polyolefin, it is not possible to obtain the effect of imparting sliding properties by forming a lubricating film. Therefore, it is important that the film contains an organic resin.

[0064] As the organic resin, at least one selected from acrylic resin, epoxy resin, polyurethane resin, phenolic resin, vinyl acetate resin and polyester resin is used. As the organic resin, two or more kinds of resins may be mixed and used.

[0065] As the acrylic resin, any acrylic resin may be used without particular limitation. Here, the acrylic resin refers to a polymer containing at least one selected from (meth)acrylic acid and (meth)acrylic acid ester as a monomer unit.

[0066] The acrylic resin preferably further contains styrene as a monomer unit. The acrylic resin containing styrene as a monomer unit has excellent water resistance and thus good rust resistance. In addition, better sliding properties can be obtained compared to the case of not containing styrene.

[0067] As the epoxy resin, any epoxy resin can be used without particular limitation. Examples of the epoxy resin include bisphenol A epoxy resin, bisphenol F epoxy resin, and novolac epoxy resin.

[0068] As the polyurethane resin, any polyurethane resin can be used without particular limitation. As the polyurethane resin, a polyurethane resin having a carboxyl group in the molecule is preferably used.

[0069] As the phenolic resin, any phenolic resin can be used without particular limitation. As the phenolic resin, a resol-based phenolic resin that is soluble or dispersible in an aqueous solvent is preferably used.

[0070] As the vinyl acetate resin, any vinyl acetate resin can be used without particular limitation. As the vinyl acetate resin, polyvinyl acetate is preferably used.

[0071] As the polyester resin, any polyester resin can be used without particular limitation. As the polyester resin, it is preferable to use a polyester resin containing a monomer having a carboxyl group as a constituent component.

[0072] From the viewpoint of film removability, the organic resin is preferably an alkali-soluble resin. That is, when the steel sheet is used for automobile bodies, etc., coating is performed after press forming. At this time, if the organic resin is an alkali-soluble resin, the film can be removed (film removal) in the alkali degreasing process performed before coating. Therefore, the subsequent coating can be performed well.

[0073] The above-mentioned film may contain an organic resin in any proportion. However, if the proportion of the organic resin is too low, the influence of components other than the organic resin becomes greater, and the effect of the organic resin is relatively reduced. Therefore, from the viewpoint of improving the effect of the organic resin, it is preferred that the proportion of the above-mentioned organic resin in the above-mentioned film is 30% or more. By making the proportion of the above-mentioned organic resin be 30% or more, the effect of improving the press moldability can be further improved, and the effects of the organic resin such as demolding properties and adhesion can be fully exerted. The proportion of the above-mentioned organic resin in the above-mentioned film is more preferably 40% or more, and further preferably 50% or more. On the other hand, there is no particular upper limit to the proportion of the above-mentioned organic resin, but in order to add a certain amount of wax as described later, it is preferably 95% or less, and more preferably 90% or less.

[0074] Here, the ratio of the organic resin in the film is defined as the ratio of the mass of the solid content of the organic resin in the film to the total mass of the total solid content in the film.

[0075] The mass average molecular weight of the organic resin is not particularly limited. However, if the mass average molecular weight is less than 5000, the rust resistance is poor sometimes. Therefore, from the viewpoint of rust resistance, the mass average molecular weight of the organic resin is preferably 5000 or more, more preferably 7000 or more, and further preferably 9000 or more. On the other hand, if the mass average molecular weight of the organic resin exceeds 30000, the adhesion is sometimes deteriorated. Therefore, from the viewpoint of adhesion, the mass average molecular weight of the organic resin is preferably 30000 or less, more preferably 25000 or less, and further preferably 20000 or less.

[0076] Here, the mass average molecular weight of the organic resin is a mass average molecular weight measured in accordance with JIS K 7252 "Plastics - Method for determining average molecular weight and molecular weight distribution of polymers by size exclusion chromatography".

[0077] (wax)

[0078] As the wax, polyolefin wax is used. Polyolefin wax has low surface energy and self-lubricating property. Therefore, by providing a film containing polyolefin wax on the surface of the base steel plate, excellent press formability can be obtained. In addition, polyolefin can be relatively easily adjusted to the melting point within the range described below by controlling the density and molecular weight. Among polyolefin waxes, polyethylene wax is preferably used because the best lubricating effect can be obtained when polyethylene wax is used.

[0079] Melting point: 100~145℃

[0080] The melting point of the polyolefin wax is 100°C to 145°C. As mentioned above, the polyolefin wax itself has self-lubricating properties. In addition, if the melting point of the polyolefin wax is within the above range, the polyolefin wax becomes semi-molten due to the frictional heat generated by the sliding of the mold during press molding, and the lubricating film formed by the mixture of organic resin and wax covers the mold surface and the sliding surface of the steel plate. As a result, the direct contact between the mold and the steel plate is suppressed, so the press moldability is significantly improved.

[0081] If the melting point of the polyolefin wax is less than 100°C, the polyolefin wax completely melts due to the frictional heat generated by sliding during press molding, so the lubricating effect of the polyolefin wax cannot be fully exerted, and the coating effect of the above-mentioned mold cannot be obtained. Therefore, the melting point of the polyolefin wax is above 100°C, preferably above 120°C. On the other hand, if the melting point of the polyolefin wax is higher than 145°C, the polyolefin wax does not melt due to the frictional heat during press molding, so not only can a sufficient lubricating effect not be obtained, but also the coating effect of the mold cannot be obtained. Therefore, the melting point of the polyolefin wax is below 145°C, preferably below 140°C.

[0082] Here, the melting point of the polyolefin wax is defined as the melting temperature measured based on JIS K 7121 "Determination of Transition Temperatures of Plastics".

[0083] Average particle size: 3.0 μm or less

[0084] If the average particle size of the polyolefin wax is greater than 3.0 μm, the polyolefin wax is easily condensed in the film, and the deviation of the film adhesion amount cannot meet the conditions described later. In addition, during the sliding of the mold during press molding, the organic resin and the wax become difficult to mix, and the coating effect of the above-mentioned mold cannot be obtained, and excellent press molding properties cannot be obtained. Therefore, the average particle size of the above-mentioned polyolefin wax is less than 3.0 μm, preferably less than 1.5 μm, more preferably less than 0.5 μm, and further preferably less than 0.3 μm. On the other hand, the lower limit of the average particle size of the polyolefin wax is not particularly limited, but if it is too small, sometimes the polyolefin wax dissolves in the lubricating oil during press molding, and the lubricity improvement effect is reduced. In addition, since the polyolefin wax is easily condensed in the coating, not only the coating stability becomes low, but also the deviation of the film adhesion amount tends to become larger. Therefore, the average particle size of the above-mentioned polyolefin wax is preferably more than 0.01 μm, more preferably more than 0.03 μm.

[0085] Here, the above average particle size can be measured by observing the wax particles on the film surface using a scanning electron microscope (SEM). That is, it is obtained by obtaining a SEM image set to a magnification corresponding to the wax particle size and performing image analysis. The average value of the equivalent circle diameter of each wax particle obtained by the above image analysis is used as the above average particle size.

[0086] Hereinafter, the method for measuring the average particle size of wax particles using SEM will be specifically described. When using SEM to measure the average particle size of wax particles, in order to suppress the diffusion and transmission of the electron beam and obtain information about the wax particles near the surface of the film, it is necessary to sufficiently reduce the acceleration voltage. For this reason, it is preferably measured at an acceleration voltage of less than 1 kV. In addition, in order to prevent image obstruction caused by charging during observation and clearly identify wax particles, it is preferred to implement a coating of conductive materials such as C, Au, and Os. The film thickness of the coating of the above-mentioned conductive material is preferably less than 2 nm. The measurement range of the SEM image must be able to identify wax particles and include a statistically significant number of wax particles. For example, when the diameter of the wax particles is 100 nm to 300 nm, it is preferred that the pixel size is less than 30 nm and the measurement range is more than 10 μm × 10 μm. It should be noted that the SEM image can be obtained by measuring multiple fields of view continuously or arbitrarily, and multiple SEM images are obtained in a manner that satisfies the above-mentioned measurement range in total.

[0087] Wax ratio: 5-70%

[0088] If the proportion of the wax in the film is less than 5%, the effect of improving the slip properties during press moldability is insufficient, and the desired press moldability cannot be obtained. Therefore, the proportion of the wax in the film is 5% or more, preferably 10% or more.

[0089] On the other hand, if the proportion of wax in the film is higher than 70%, the proportion of organic resin as a binder is relatively reduced, resulting in reduced adhesion to the steel plate and impaired adhesion. In addition, since the wax component is easy to fall off, the deviation of the film adhesion amount cannot be reduced to the desired range. Furthermore, when coating is implemented, the film is not fully stripped from the surface of the steel plate in the alkali degreasing process, and sufficient degreasing cannot be obtained, resulting in deterioration of coating properties. Therefore, the proportion of wax in the above-mentioned film is less than 70%, preferably less than 50%, and more preferably less than 30%.

[0090] Here, the ratio of the wax in the film is defined as the ratio of the mass of the solid content of the wax in the film to the total mass of the total solid content in the film.

[0091] (Deviation in film adhesion amount)

[0092] As described above, when the coated steel sheet formed with the film containing organic resin and wax is press-formed, the film contacts and slides with the mold surface, thereby forming a lubricating film on the sliding surface of the mold surface and the steel sheet. As a result, the friction coefficient is reduced and the press-formability is improved. At this time, since there are unevenness on the surface of the base steel sheet, the contact with the above-mentioned mold mainly occurs at the convex part of the steel sheet surface, that is, the part with high height of the steel sheet.

[0093] On the other hand, when coating is applied to the surface of a steel plate to form a film, the coating tends to accumulate in the concave portion of the base steel plate, i.e., the portion where the height of the steel plate is low. As a result, the amount of film attached to the convex portion of the steel plate decreases, while the amount of film attached to the concave portion of the steel plate increases. In this way, the overall amount of film attached varies in the obtained film.

[0094] In addition, the film adhesion amount also varies locally (microscopically) due to the effects of condensation of wax and organic resin, etc. Therefore, the final film has both overall and local variations in the film adhesion amount.

[0095] Therefore, even if the overall coating amount has a small deviation, if the local coating amount has a large deviation, there will be a region with a very small coating amount on the convex portion of the steel plate. In this case, a sufficient amount of coating components will not be supplied to the convex portion of the steel plate during press forming, so the effect of reducing the friction coefficient cannot be fully obtained, and as a result, good press formability cannot be obtained.

[0096] Therefore, the present inventors studied a method for evaluating the influence of the above-mentioned local deviation of the coating adhesion amount. First, an attempt was made to evaluate the deviation of the coating adhesion amount using the standard deviation. However, as a result, no clear correlation was found between the standard deviation and the press formability. It is believed that this is because the standard deviation is greatly affected by the deviation of the overall coating adhesion amount, and the method using the standard deviation cannot appropriately evaluate the influence of the deviation of the local coating adhesion amount.

[0097] Therefore, the inventors studied a method of eliminating the influence of the overall film coating amount variation and evaluating the local film coating amount variation. As a result, they found that there is a correlation between the film coating amount variation σ' defined by the following formula (1) and press formability.

[0098]

[0099] Among them, W i : The amount of film deposited at the measuring point i (g / m 2 ),

[0100] H i : The height of the base steel plate at the measuring point i,

[0101] μ W : The amount of film attached,

[0102] μ H : The average value of the height of the above-mentioned base steel plate,

[0103] a: the slope of the regression line in the scatter plot obtained by plotting the amount of the coating against the height of the base steel plate,

[0104] b: The intercept of the above regression line.

[0105] σ': 0.300 or less

[0106] If the deviation σ' of the above-mentioned film adhesion amount is greater than 0.300, the deviation of the film adhesion amount of the convex part of the steel plate becomes larger, forming an area with very little film adhesion. As a result, the mold surface and the sliding surface of the steel plate are not covered with a sufficient amount of lubricating film, and the desired press formability cannot be obtained. Therefore, σ' is set to be less than 0.300, preferably less than 0.275, and more preferably less than 0.260. On the other hand, from the viewpoint of press formability, the smaller the deviation of the film adhesion amount, the better, so the lower limit of σ' is not particularly limited. However, from the viewpoint of industrial production, σ' can be, for example, greater than 0.100.

[0107] The above-mentioned deviation σ' of the coating amount can be obtained by obtaining a coating amount map and a steel plate height map and analyzing them. The specific procedure is described below.

[0108] First, obtain a diagram of the coating adhesion of the coated steel plate. The above-mentioned coating adhesion diagram can be obtained by measuring the intensity of characteristic X-rays generated when the coating is irradiated with electron beams. In the above-mentioned measurement, a scanning electron microscope (SEM) or an electron beam microanalyzer (EPMA) equipped with an X-ray spectrometer can be used. First, using characteristic X-rays, the intensity diagrams of Kα rays of carbon (C), which is the main component of the coating, and Lα rays of iron (Fe), which is the main component of the steel plate, are measured respectively. The ratio of C intensity to Fe intensity (C / Fe intensity ratio) at each measurement point is calculated, and a C / Fe intensity ratio diagram is prepared.

[0109] Next, a coating adhesion amount graph is prepared using a pre-prepared calibration curve based on the above C / Fe intensity ratio graph. That is, the average value of the C / Fe intensity ratio is roughly proportional to the coating adhesion amount. Therefore, a calibration curve for converting the C / Fe intensity ratio into the coating adhesion amount is prepared using a plurality of coated steel sheets having a coating with a known coating adhesion amount. Specifically, the C intensity and Fe intensity of the above coated steel sheets are measured, the average value of the C / Fe intensity ratio is calculated, and a calibration curve is prepared based on the relationship between the obtained average value of the C / Fe intensity ratio and the coating adhesion amount.

[0110] When using characteristic X-rays to prepare the above-mentioned coating adhesion map, it is necessary to sufficiently increase the acceleration voltage so that the incident electrons can reach the steel plate even in the concave part of the steel plate where the coating adhesion is large, and generate Fe Lα rays of sufficient intensity. For this reason, it is preferable to set the acceleration voltage to 10 kV or more. However, if the acceleration voltage is too high, the generation efficiency of C Kα rays decreases and the intensity decreases, so the acceleration voltage is preferably set to 20 kV or less.

[0111] In addition, the measurement range and analysis point size of the above-mentioned intensity diagram need to be set to the condition of a size that is statistically significant relative to the concave-convex shape of the steel plate surface. When the surface roughness (arithmetic mean roughness Ra) of the steel plate is about 1μm, the diameter of the convex part of the steel plate is about 50μm. Therefore, the measurement range is expected to be about 300μm×300μm, so that more than 10 convex parts of the steel plate are included in the measurement range. In addition, the above-mentioned analysis point size is expected to be less than 10μm, so that more than 10 points can be measured on each convex part of the steel plate. It should be noted that the above-mentioned intensity diagram can be obtained by measuring a continuous or arbitrary plurality of fields of view, and is composed of a plurality of intensity diagrams in a manner that satisfies the above-mentioned measurement range in total.

[0112] Next, obtain a steel plate height map. The steel plate height can be measured using, for example, a white interferometer or a laser microscope as a shape measuring device. The steel plate height map is obtained in the same field of view as the film adhesion amount map. The measurement range and analysis point size of the height map are preferably consistent with the measurement conditions of the film adhesion amount. In the case of an opaque film, the above measurement can be performed after removing the film to obtain a steel plate height map. The peeling of the film can be performed by the same method as the measurement of the film adhesion amount described later.

[0113] Next, the obtained coating adhesion amount map and steel plate height map are aligned, and the number of pixels and pixel size of the measurement data (coating adhesion amount data and steel plate height data) of each measurement point are adjusted. The above alignment is not particularly limited, and can be performed manually or using image processing software. In addition, the adjustment of the number of pixels and pixel size of the measurement data is not particularly limited, and can be implemented by linear interpolation using image processing software, for example.

[0114] Next, in order to obtain σ', a scatter plot of the coating amount versus the steel plate height is prepared using the coating amount data and the steel plate height data calculated at the same measurement point as described above. An example of the scatter plot is shown in FIG. Figure 1 A linear regression is performed on the scatter plot to obtain a regression line represented by the following equation (2).

[0115] W=aH+b…(2)

[0116] Here, W is the coating adhesion amount, H is the steel plate height, a is the slope of the regression line, and b is the intercept of the regression line.

[0117] Next, the measured film adhesion amount and steel plate height data and the film adhesion amount μ W , the slope a and intercept b of the above regression curve, and σ' is calculated by the above formula (1). That is, for each measuring point i, the height H of the steel plate at the measuring point i is obtained. i The value of W (aH) calculated by the above formula (2) i + b) and the actual film adhesion amount Wi at the measurement point i {W i -(aH i +b)}. Then, from the above {W i -(aH i + b)}, the adhesion amount of the above film μ W and the average value μ of the height of the above-mentioned base steel plate H The standard deviation is calculated by dividing the obtained standard deviation by the coating adhesion amount μ W By using this σ', the influence of the overall film adhesion amount deviation can be eliminated and the local adhesion amount deviation can be evaluated. W The determination method is described later.

[0118] [Rust inhibitor]

[0119] The film does not rust under normal storage environment even when it does not contain a rust inhibitor. However, from the viewpoint of further improving the rust resistance, the film preferably further contains a rust inhibitor.

[0120] As the above-mentioned rust inhibitor, any rust inhibitor can be used without particular limitation, and preferably at least one selected from aluminum salts, zinc salts and zinc oxide of phosphoric acid is used. Here, phosphoric acid includes condensed phosphoric acids such as pyrophosphoric acid, tripolyphosphoric acid, tetrapolyphosphoric acid and metaphosphoric acid in addition to orthophosphoric acid. By using these rust inhibitors, a more excellent rust-proof effect can be exerted, and the deterioration of the coating stability is also small.

[0121] The content of the rust inhibitor is not particularly limited, but if the content of the rust inhibitor is too low, sometimes a sufficient effect cannot be obtained. In particular, when the coated steel sheets are stored in a coiled state, they are prone to rust due to moisture absorption. From the viewpoint of preventing rust even in such a harsh environment, it is preferred that the proportion of the rust inhibitor in the film is 5% or more. On the other hand, if the proportion of the rust inhibitor in the film exceeds 30%, sometimes the adhesion is deteriorated. In addition, sometimes the rust inhibitor precipitates in the state of the paint, and the paint stability is deteriorated. Therefore, it is preferred that the proportion of the rust inhibitor in the film is 30% or less.

[0122] Here, the ratio of the rust inhibitor in the film is defined as the ratio of the mass of the rust inhibitor in the film to the total mass of the total solid content in the film.

[0123] [Dispersant]

[0124] From the viewpoint of improving the dispersibility of the film components, the film preferably further contains a dispersant. As the dispersant, any dispersant can be used without particular limitation, and an anionic polymer dispersant is preferably used. In addition to being particularly effective in improving the dispersibility of particles of a few μm or less, anionic polymer dispersants can also be adsorbed on polyolefin wax. As the anionic polymer dispersant, at least one selected from sodium polycarboxylate, sodium polyacrylate, carboxylic acid copolymer and sulfonic acid copolymer is preferably used.

[0125] The proportion of the dispersant in the film is not particularly limited, but is preferably 0.5% or more. If the proportion of the dispersant in the film is 0.5% or more, the dispersibility of the wax in the coating is improved, and the uniformity of the wax distribution in the obtained film is improved. As a result, it is easy to reduce the deviation of the local (microscopic) film adhesion amount, and the compression molding property is further improved. On the other hand, if the proportion of the dispersant in the film exceeds 5%, the adhesion is sometimes deteriorated. Therefore, the proportion of the dispersant in the film is preferably 5% or less.

[0126] Here, the ratio of the dispersant in the film refers to the ratio of the mass of the dispersant in the film to the total mass of the solid content of all components in the film.

[0127] (Silicon Dioxide)

[0128] From the viewpoint of improving the water resistance and rust resistance of the film, it is preferred that the film further contains silicon dioxide. In addition, by containing silicon dioxide, the precipitation of the rust inhibitor contained in the coating can be suppressed, thereby improving the coating stability.

[0129] As the above-mentioned silica, any silica can be used without particular limitation. As the above-mentioned silica, colloidal silica is preferably used. The average particle size of the above-mentioned colloidal silica is not particularly limited, and is preferably above 5 nm. In addition, the average particle size of the above-mentioned colloidal silica is preferably below 200 nm. The average particle size of the above-mentioned colloidal silica can be measured by a dynamic light scattering method. Specifically, first, the particle size distribution under the scattering intensity standard is measured by a dynamic light scattering method. Then, the above-mentioned particle size distribution is converted from the scattering intensity standard to the volume standard. The median particle size D50 in the obtained volume-based particle size distribution is taken as the average particle size of the colloidal silica.

[0130] The proportion of silicon dioxide in the above-mentioned film is preferably 1% or more. By making the proportion of silicon dioxide in the film more than 1%, the waterproofness of the film is improved and the rust resistance is further improved. In addition, on the other hand, if the proportion of silicon dioxide in the film exceeds 10%, the adhesiveness sometimes deteriorates. Therefore, the proportion of silicon dioxide in the above-mentioned film is preferably less than 10%.

[0131] Here, the ratio of silicon dioxide in the film refers to the ratio of the mass of silicon dioxide in the film to the total mass of the solid content of all components in the film.

[0132] The ratio of each component contained in the above-mentioned film can be calculated from the solid content mass of each film component when the coating material is prepared.

[0133] The film may contain other optional components in addition to the organic resin, wax, rust inhibitor, dispersant and silica. Examples of the other components include surface conditioners and defoamers that are usually added to paint.

[0134] The amount of film attached μ W : 0.3g / m 2 above

[0135] When the coating adhesion μ W Less than 0.3g / m 2 When the coating is applied to form the film, wax condensation is likely to occur during the period from coating to drying, so the local (microscopic) deviation of the film adhesion amount increases, resulting in a decrease in press formability. W 0.3g / m 2 It should be noted that, as described above, the overall deviation of the coating adhesion amount is affected by the surface roughness of the base steel plate. Therefore, from the viewpoint of reducing the local (microscopic) deviation of the coating adhesion amount even when the surface roughness of the base steel plate is large, it is preferred to set the coating adhesion amount μ W 0.4g / m 2 More preferably 0.6 g / m 2 More preferably, 0.8 g / m 2 On the other hand, μ W There is no particular upper limit, but if it exceeds 2.5 g / m 2 , sometimes the weldability, demolding property and adhesiveness are deteriorated. W Preferably 2.5g / m 2 It should be noted that the coating adhesion amount μ W It is defined as the value on a single side of a steel plate.

[0136] The amount of film attached μ WIt can be obtained by removing the film from the coated steel plate and dividing the mass difference before and after the film is removed by the area of ​​the steel plate. The film can be removed by any method as long as it is a method that can remove only the film without damaging the base steel plate. Typically, a solvent (organic solvent, etc.) that can dissolve the organic resin constituting the film, a stripping agent containing the above solvent, etc. can be used. When the above film is alkali-soluble, as described in the examples, it is preferred to use an alkali degreasing agent.

[0137] [Base steel plate]

[0138] As described above, in the present invention, excellent press formability is achieved by controlling the composition of the film and the distribution of the wax in the film. Therefore, any steel plate can be used as the base steel plate without particular limitation. The base steel plate can be a cold-rolled steel plate or a hot-rolled steel plate.

[0139] The tensile strength TS of the above-mentioned base steel plate is not particularly limited, but if it is too low, the strength of the finally obtained press-formed part is sometimes insufficient. Therefore, the tensile strength of the above-mentioned base steel plate is preferably above 260MPa. On the other hand, the upper limit of the above-mentioned tensile strength is not particularly limited. For example, when a high-strength steel plate with a tensile strength of more than 440MPa is used as the base steel plate, the surface pressure during press forming becomes high. However, according to the present invention, the friction coefficient between the steel plate and the mold can be significantly reduced, so even under such high surface pressure conditions, the generation of cracks and mold wear can be suppressed, and good press formability can be obtained. Therefore, the tensile strength of the base steel plate can be more than 440MPa. However, if the tensile strength is too high, it is difficult to press form into a complex shape. Therefore, from the viewpoint of press formability to complex shapes, the tensile strength of the above-mentioned base steel plate is preferably below 440MPa.

[0140] The thickness of the base steel plate is not particularly limited, but if it is too thin, the strength of the final press-formed part may be insufficient. Therefore, the thickness of the base steel plate is preferably 0.5 mm or more. On the other hand, the upper limit of the thickness is not particularly limited, but if it is too thick, it is difficult to press-form into a complex shape. Therefore, the thickness of the base steel plate is preferably 4.0 mm or less.

[0141] The surface roughness of the above-mentioned base steel plate (the surface roughness of the base steel plate before the film is formed) is not particularly limited. However, when the arithmetic mean roughness Ra of the base steel plate surface is greater than 2.5μm, the surface of the base steel plate is large, so the film formed in the concave portion is difficult to contact the mold during press forming. In addition, in the convex portion, the amount of film adhesion is less than that in the concave portion, so the deviation of the local (microscopic) film adhesion amount increases, and as a result, the effect of improving the press formability is sometimes reduced. Therefore, from the viewpoint of further improving the press formability, it is preferred that Ra is less than 2.5μm. On the other hand, when Ra is less than 0.4μm, fine scratches that may be generated during press forming are easily conspicuous. In addition, if Ra is less than 0.4μm, wear sometimes occurs during press forming. Therefore, Ra is preferably above 0.4μm.

[0142] Here, the arithmetic mean roughness Ra of the base steel plate can be measured in accordance with JIS B 0633: 2001 (ISO 4288: 1996). For example, when Ra is greater than 0.1 and less than 2, the cutoff value and the reference length are set to 0.8 mm, the evaluation length is set to 4 mm, and Ra is obtained from the measured roughness curve. When Ra is greater than 2 and less than 10, the cutoff value and the reference length are set to 2.5 mm, the evaluation length is set to 12.5 mm, and Ra is obtained from the measured roughness curve.

[0143] (2) Manufacturing method

[0144] Next, the manufacturing method of the coated steel sheet of the present invention is described. In one embodiment of the present invention, the coated steel sheet is manufactured by applying a coating containing an organic resin and a wax to at least one surface of a base steel sheet and drying it. It should be noted that the points not specifically mentioned may be the same as the description of the coated steel sheet.

[0145] As the coating, for example, a coating obtained by adding wax to an organic resin solution in which an organic resin is dissolved in a solvent or an organic resin emulsion in which an organic resin is dispersed in a solvent can be used. As the solvent, one or both of water and an organic solvent can be used, but water is preferably used.

[0146] The ratio of the total solid content in the coating is not particularly limited, but is preferably 1 to 30%. When the ratio of the total solid content in the coating is less than 1% or exceeds 30%, uneven coating may occur, and the desired wax distribution may not be obtained. It should be noted that the ratio of the total solid content in the coating here refers to the concentration of the total solid content in the coating, that is, the ratio of the solid content mass to the total mass of the coating (including the solvent).

[0147] The coating on the base steel sheet can be applied by any method without particular limitation. Examples of the above-mentioned coating include methods using a roll coater, a rod coater, spraying, dipping, brushing, and the like. In the above-mentioned coating, in the finally obtained coated steel sheet, the coating adhesion amount on one side of the steel sheet is 0.3 g / m2 in terms of dry mass. 2 The coating material is applied in the above manner.

[0148] Drying after coating is applied may be performed by any method without particular limitation. Examples of the drying method include drying with hot air, drying with an IH heater, and a method using infrared heating.

[0149] The maximum temperature of the steel plate during drying is preferably 60°C to the melting point of the wax used. If the maximum temperature is less than 60°C, drying takes time and the rust resistance is sometimes poor. On the other hand, when the maximum temperature exceeds the melting point of the wax, the wax melts and coalesces, and the particle size coarsens, thereby easily increasing the deviation of the local (microscopic) film adhesion amount.

[0150] Example

[0151] Hereinafter, the present invention will be described by way of examples, but it should be noted that the present invention is not limited to the following examples.

[0152] A coated steel sheet is produced by forming a coating on the surface of a base steel sheet in the following steps.

[0153] First, four types of base steel plates having arithmetic mean roughness Ra shown in Table 1 were prepared. Base steel plates A to C were cold-rolled steel plates with a plate thickness of 0.8 mm, and base steel plate D was a hot-rolled steel plate with a plate thickness of 2.0 mm. It should be noted that base steel plates A to D were all SPCD (JIS G 3141) and SPHD (JIS G 3131) having a tensile strength of 270 MPa.

[0154] In addition, coatings of the compositions shown in Tables 2 and 3 were prepared. The ratio of each component in Tables 2 and 3 is the ratio of the mass of the solid content of each component contained in the coating to the total mass of the total solid content. It should be noted that colloidal silica with a volume average particle size of 9 nm was used as silica. In addition, the molecular weight of the organic resin shown in Tables 2 and 3 and the melting point and average particle size of the wax are values ​​measured by the above method, respectively.

[0155] The coating was applied to the surface of the base steel plate using a bar coater, and heated and dried using an IH heater so that the maximum temperature of the steel plate surface reached 80°C to obtain a coated steel plate. The combinations of the base steel plate and the coating used are shown in Tables 4 to 7. It should be noted that, for comparison, in some comparative examples, the coating was not formed, and the base steel plate was directly used for the evaluation described below.

[0156] (Film adhesion amount)

[0157] The amount of film adhesion in the obtained coated steel plate is measured. Specifically, the film is removed from the coated steel plate, and the mass difference before and after the film removal is divided by the area of ​​the steel plate to calculate the adhesion amount. The removal of the above-mentioned film is carried out by immersing the coated steel plate in a degreasing solution with a degreasing agent concentration of 20 g / L and a temperature of 40°C for 300 seconds. As the above-mentioned degreasing agent, FINE CLEANER E6403 (manufactured by Nihon Parkerizing Co., Ltd.), an alkaline degreasing agent, is used. It should be noted that the film is completely removed under the above-mentioned conditions by the same method as the film removability test described later. The film adhesion amounts shown in Tables 4 to 7 are the values ​​on a single side of the steel plate.

[0158] (Deviation in film adhesion amount)

[0159] Next, the variation in the coating adhesion amount of the obtained coated steel sheets was evaluated in the following procedure.

[0160] First, five test pieces of 10 mm × 10 mm in size were cut from each of the coated steel sheets. The center of the test piece was measured using a Schottky field emission SEM (Σigma manufactured by Carl Zeiss) equipped with an energy dispersive X-ray spectrometer (XFlash6|30 manufactured by Burker) to obtain intensity maps of Kα rays of C and Lα rays of Fe. The above measurement was performed by EDS mapping under the conditions of a magnification of 200 times, an acceleration voltage of 15 kV, and a resolution of 800 × 600.

[0161] The obtained C Kα ray intensity map was divided by the corresponding Fe Lα ray intensity map to create a C Kα / Fe Lα intensity ratio map. The intensity ratio map was then converted into an adhesion amount using a previously created calibration curve to create a film adhesion amount map.

[0162] On the other hand, the height of the steel plate is measured using a laser microscope (VK-X105 manufactured by Keyence). In the same field of view as when measuring the above intensity map, a height map with an objective lens magnification of 20 times is measured at a resolution of 2048×1536. Then, image alignment and resolution adjustment are performed using image processing software to calculate the amount of film adhesion and the height of the steel plate at the same point. It should be noted that since the film of the coated steel plate used in this embodiment is transparent, the height measurement of the above steel plate is implemented in the presence of the film.

[0163] A scatter plot is made based on the obtained coating adhesion amount and steel plate height at the same point, and its regression line is obtained. The value at the steel plate height of each point of the obtained regression line is taken as the average value of the coating adhesion amount corresponding to the steel plate height, and it is subtracted from the coating adhesion amount at each point, thereby obtaining the difference between the average values ​​of the coating adhesion amount corresponding to the steel plate height and its standard deviation. The standard deviation is divided by the coating adhesion amount of the entire field of view to calculate σ'. It should be noted that when calculating the above σ', the measurement data of all 5 test pieces are used.

[0164] Next, the properties of the obtained coated steel sheets were evaluated according to the following procedures.

[0165] (Pressing Formability)

[0166] Press formability is related to sliding property, that is, the friction coefficient of the steel sheet surface. The lower the friction coefficient, the better the press formability. Therefore, in order to evaluate press formability, the friction coefficient of the obtained coated steel sheet was measured according to the following procedure.

[0167] Figure 2 : is a schematic front view showing a friction coefficient measuring device. As shown in the figure, a friction coefficient measuring sample 1 taken from a coated steel plate is fixed to a sample stand 2, and the sample stand 2 is fixed to the upper surface of a horizontally movable slide table 3. A slide table support 5 having a roller 4 connected thereto and movable up and down is provided on the lower surface of the slide table 3, and a first load cell 7 is mounted on the slide table support 5. The first load cell 7 is used to measure the push load N on the friction coefficient measuring sample 1 generated by the flange 6 by pushing the slide table support 5 upward. A second load cell 8 is mounted on one end of the slide table 3. The second load cell 8 is used to measure the sliding resistance F when the slide table 3 is moved in the horizontal direction under the condition that the above-mentioned push force is applied. It should be noted that the test was conducted by applying PRETON R352L, a cleaning oil for pressing made by SUGIMURA Chemical Industrial Co., Ltd., to the surface of the sample 1 as a lubricating oil.

[0168] Figure 3 1 is a schematic perspective view showing the shape and size of the flange used. The lower surface of the flange 6 slides while being pressed against the surface of the sample 1 . Figure 3 The shape of the flange 6 shown is 10 mm wide and 59 mm long in the sliding direction of the sample. The lower parts of both ends in the sliding direction are composed of curved surfaces with a curvature of 4.5 mmR. The lower surface of the flange that pushes the sample has a flat surface with a width of 10 mm and a length of 50 mm in the sliding direction.

[0169] Friction coefficient test Figure 3The flange shown was tested at a push load of 400 kgf and a sample pulling speed (horizontal moving speed of the slide table 3) of 20 cm / min. The friction coefficient μ between the sample and the flange was calculated by the formula: μ=F / N.

[0170] The obtained friction coefficient values ​​are shown in Tables 4 to 7. When the friction coefficient was 0.115 or less, the press moldability (sliding property) was judged to be good.

[0171] (Weldability)

[0172] When the press-formed parts obtained by press-forming the coated steel sheet are used for automobile bodies, etc., welding is usually performed in the assembly process. Therefore, the coated steel sheet is expected to have excellent weldability in addition to press-formability. Therefore, the weldability of the coated steel sheet is evaluated. Specifically, a continuous spot welding test is performed on the coated steel sheet under the conditions of using electrode: DR type Cr-Cu electrode, pressure: 150kgf, power-on time: 10 cycles / 60Hz, welding current: 7.5kA, and the number of continuous spots is calculated. When the number of continuous spots is 5000 or more, the weldability is evaluated as "good", and when it is less than 5000 points, the weldability is evaluated as "inadequate".

[0173] (Releasability)

[0174] Assuming that the coated steel sheet of the present invention is used for automobile applications, the removability during degreasing was evaluated. In order to determine the removability of the coating, each coated steel sheet was first immersed in a degreasing liquid having a degreasing agent concentration of 20 g / L and a temperature of 40° C. for a predetermined period of time, and then washed with tap water to perform degreasing. As the degreasing agent, FINECLEANER E6403 (manufactured by Nihon Parkerizing Co., Ltd.), which is an alkaline degreasing agent, was used.

[0175] Next, the surface carbon intensity of the degreased test piece was measured using a fluorescent X-ray analyzer. The film peeling rate was calculated using the following formula using the measured surface carbon intensity, the previously measured surface carbon intensity before degreasing, and the surface carbon intensity of the base steel plate.

[0176] Film peeling rate (%) = [(surface carbon strength before degreasing - surface carbon strength after degreasing) / (surface carbon strength before degreasing - surface carbon strength of base steel plate)] × 100

[0177] It should be noted that the surface carbon strength of the base steel plate herein refers to the surface carbon strength of the base steel plate before the film is formed.

[0178] The above test was conducted by changing the immersion time in the degreasing solution to obtain the immersion time in the alkaline degreasing solution at which the film peeling rate was 98% or more. The obtained immersion time was shown as "film stripping time" in Tables 4 to 7. When the above film stripping time was 120 seconds or less, it was evaluated as good film stripping property.

[0179] (Rust resistance)

[0180] Assuming that the coated steel sheet is stored in a coiled state, the rust resistance in the overlapped state was evaluated. Specifically, a test piece of 150 mm × 70 mm in size was taken from the coated steel sheet, and the surface of the test piece was coated with 1.0 g / m 2 Then, the two test pieces were overlapped and the surface pressure was 0.02 kgf / mm. 2 The load was applied and the test piece was kept in an environment of a temperature of 50° C. and a humidity of 95% RH.

[0181] The inner side of the overlapped surface was checked every 7 days, and the number of days until rusting was evaluated. The case where the number of days until rusting was 56 days or more was evaluated as "excellent", the case where it was 21 days or more was evaluated as "good", and the case where it was less than 21 days was evaluated as "acceptable".

[0182] (Adhesion)

[0183] When the press-formed parts obtained by press-forming the coated steel sheet are used for automobile bodies, etc., bonding is sometimes performed during the assembly process. Therefore, the coated steel sheet is expected to have excellent adhesion in addition to press-formability. Therefore, the adhesion of the coated steel sheet is evaluated. Specifically, two test pieces of 100×25.4 mm in size are taken from each coated steel sheet and immersed in rust-proof oil. After the above-mentioned test piece is pulled up from the rust-proof oil, it is vertically stood for 24 hours to remove excess oil.

[0184] Next, an epoxy adhesive was uniformly applied to the surface of the test piece in an area of ​​25.4 mm × 13 mm with a thickness of 0.2 mm. Then, two test pieces were overlapped and clamped with a clip, and baked at 180°C for 20 minutes to dry and cure. After cooling, a shear tensile test was performed using an AUTOGRAPH testing machine to measure the shear adhesion. When the shear adhesion was 20 MPa or more, it was rated as good adhesion.

[0185] From the results shown in Tables 4 to 7, it can be seen that the friction coefficients of the coated steel sheets satisfying the conditions of the present invention are all below 0.115, and they have excellent press formability. In contrast, the friction coefficients of the coated steel sheets not satisfying the conditions of the present invention are all above 0.115, and they have poor press formability.

[0186] As described above, the coated steel sheet of the present invention is excellent in sliding property (press formability) during press forming and can be suitably used for various applications including automobile body applications.

[0187] surface

[0188]

[0189]

[0190]

[0191]

[0192]

[0193]

[0194]

[0195] Explanation of symbols

[0196] 1. Specimen for determination of friction coefficient

[0197] 2. Sample table

[0198] 3 Sliding table

[0199] 4 Rollers

[0200] 5 Sliding table support

[0201] 6 Flange

[0202] 7First weighing sensor

[0203] 8 Second load cell

[0204] 9 rails

Claims

1. A coated steel sheet comprising a base steel sheet and a coating film containing an organic resin and a wax provided on at least one surface of the base steel sheet, wherein: The organic resin is at least one selected from acrylic resin, epoxy resin, polyurethane resin, phenolic resin, vinyl acetate resin and polyester resin. The wax is a polyolefin wax having a melting point of 100° C. to 145° C. and an average particle size of 3.0 μm or less. The ratio of the wax in the film is 5% to 70% by mass. The deviation σ' of the coating adhesion amount defined by the following formula (1) is 0.300 or less. The coating adhesion μ W 0.3g / m 2 above, in, W i : The amount of film adhered at the measuring point i, in g / m 2 , H i : The height of the base steel plate at the measuring point i, μ W : The amount of film attached, μ H : The average value of the height of the base steel plate, a: the slope of the regression line in the scatter plot obtained by plotting the amount of the coating against the height of the base steel plate, b: intercept of the regression line.

2. The coated steel sheet according to claim 1, wherein: The ratio of the organic resin in the film is 30% by mass to 95% by mass. The ratio of the wax in the film is 5% by mass to 50% by mass.

3. The coated steel sheet according to claim 1 or 2, wherein: The arithmetic mean roughness Ra of the surface of the base steel plate is 0.4 μm to 2.5 μm.

4. The coated steel sheet according to any one of claims 1 to 3, wherein The coating adhesion μ W 2.5g / m 2 the following.

5. The coated steel sheet according to any one of claims 1 to 4, wherein The organic resin is an alkali-soluble resin.

6. The coated steel sheet according to any one of claims 1 to 5, wherein The film further contains a rust inhibitor.

7. The coated steel sheet according to claim 6, wherein: The rust inhibitor is at least one selected from aluminum salts, zinc salts and zinc oxide of phosphoric acid.

8. The coated steel sheet according to any one of claims 1 to 7, wherein The film further contains a dispersant.

9. The coated steel sheet according to claim 8, wherein: The dispersant is at least one selected from sodium polycarboxylate, sodium polyacrylate, carboxylic acid copolymer and sulfonic acid copolymer.

10. The coated steel sheet according to any one of claims 1 to 9, wherein The film further contains silicon dioxide.

11. A method for producing a coated steel sheet according to any one of claims 1 to 10, comprising applying a coating comprising an organic resin and a wax to at least one surface of a base steel sheet and drying the coating, wherein: The organic resin is at least one selected from acrylic resin, epoxy resin, polyurethane resin, phenolic resin, vinyl acetate resin and polyester resin. The wax is a polyolefin wax having a melting point of 100° C. to 145° C. and an average particle size of 3.0 μm or less.

12. The method for producing a coated steel sheet according to claim 11, wherein: The maximum reaching temperature of the base steel sheet during the drying is 60° C. or higher and equal to or lower than the melting point of the wax.

13. The method for producing a coated steel sheet according to claim 11 or 12, wherein: The ratio of the total solid content in the coating material is 1% by mass to 30% by mass.

Citation Information

Patent Citations

  • Coated steel plate

    CN101466871A

  • Black metal sheet

    CN102791478A

  • Resin-coated metal sheet and resin composition

    CN1907579A

  • Resin-coated metal sheet and resin composition

    EP1749866A1

  • Non-oil coat type organic substance coated metal plate excellent in press processability and heat resistance after processing

    JP1996192102A